Analysis Of Marketing Strategies Of Post Covid-19 Bromelia Ornamental Plants In Tamansari District, Bogor Regency - Adinda Lifstania; Abubakar Abubakar; Muhamad Rom Ali Fikri (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This research aims to identify and analyze the main factors in Bromelia farmer production, formulate strategies, and determine priority strategies. Methodology: The research method used is descriptive analytical which is qualitative and quantitative. Primary data was obtained through interviews and questionnaires, secondary data through literature studies of relevant journals as well as BPS and local government data. Sampling was carried out by purposive sampling, the number of samples used was 20 people. Data analysis uses the Internal Factors Evaluation (IFE), External Factors Evaluation (EFE), Internal-External (IE) Matrix, SWOT Matrix, and QSPM Matrix. Results: The results of this research show that the main internal factor is that the location/village is already famous for its plant symbol. ornamental with a score of 0.42 and the main external factor is the demand for Bromeliads to date due to price stability. Finding: the potential for ornamental plant centers in Tamansari District, as well as price competition between farms of different plant types with a score of 0.341. Novelty : The resulting priority strategy The QSPM matrix with a STAS value (5.69) is to expand the reach and introduce Bromeliad plants to be able to collaborate with stakeholders. Type of Paper: Identifisuch as a research article.